Polygalactan from bivalve Crassostrea madrasensis attenuates nuclear factor-κB activation and cytokine production in lipopolysaccharide-activated macrophage. (1st December 2020) - Chakraborty, Kajal; Krishnan, Soumya; Joy, Minju
Graphical abstract: Highlights: A sulfated polygalactan -was isolated from bivalve oyster Crassostrea madrasensis . Sulfated polygalactan displayed dual inhibitory effects against COX-2 and 5-LOX. Studied compound attenuated NF- κ B signaling cascade in LPS-activated macrophages. Studied compound suppressed the generation of cytokines and reactive oxygen species. Abstract: A polygalactosamino-glucopyranosyl fucopyranose →4)- β -GlcA p {(3→1)- α -Fuc p } -β -Gal N Ac p -(4, 6-SO3 − )-(1→ isolated from the bivalve Crassostrea madrasensis exhibited prospective anti-inflammatory activity against cyclooxygenase-2 and 5-lipoxygenase (IC50 < 50 μg mL −1 ) on lipopolysaccharide-induced macrophages. The polygalactan attenuated inducible nitric oxide synthase (IC50 65.7 μg mL −1 ) in lipopolysaccharide-prompted inflammation leading to the reduction of pro-inflammatory cytokine nitric oxide (236.2 μg mL −1 lysate), nuclear factor- κ B, tumor necrosis factor- α, and interleukins (0.19−0.22 units mg −1 protein at 100 μg mL -1 ) by inhibiting cyclooxygenase-2. The polygalacatan suppressed the mRNA of nuclear factor- κ B and cyclooxygenase-2 in lipopolysaccharide-induced macrophages. Western blot experiment revealed that the polygalactan attenuated the migration of nuclear factor- κ B-p 65 to the nucleus from cytoplasm, and suppressed the phosphorylation of α -subunit of κ B inhibitor. Greater selectivity index of sulfated polygalactan (3.93) towards inducible cyclooxygenase-2 as compared with the anti-inflammatory agent ibuprofen (1.11), and the potential to inhibit nuclear factor- κ B cascade to generate chemokine production manifested its utilization in the development of functional food attenuating inflammation-related disorders.